Novel role of group VIB Ca2+-independent phospholipase A2γ in leukocyte-endothelial cell interactions: An intravital microscopic study in rat mesentery. Issue 5 (November 2015) - Kojima, Mitsuaki; Aiboshi, Junichi; Shibata, Masahiro; Kobayashi, Tetsuyuki; Otomo, Yasuhiro
Abstract : BACKGROUND: Phospholipase A2 (PLA2 ) is associated with a variety of inflammatory processes related to polymorphonuclear neutrophil (PMN)–endothelial cell interactions. However, the cellular and molecular mechanisms underlying the interactions and the causative isoform(s) of PLA2 remain elusive. In addition, we recently showed that calcium-independent PLA2 γ (iPLA2 γ), but not cytosolic PLA2 (cPLA2 ), is responsible for the cytotoxic functions of human PMN including respiratory bursts, degranulation, and chemotaxis. We therefore hypothesized that iPLA2 γ is a prerequisite for the PMN recruitment cascade into the site of inflammation. The aim of this study was to elucidate the roles of the three major phospholipases A2, iPLA2, cPLA2 and secretory PLA2, in leukocyte rolling and adherence and in the surface expression of β2 -integrins in vivo and in vitro in response to well-defined stimuli. METHODS: Male Wistar rats were pretreated with PLA2 inhibitors selective for iPLA2 β, iPLA2 γ, cPLA2, or secretory PLA2 . Leukocyte rolling/adherence in the mesenteric venules superfused with platelet-activating factor (PAF) were quantified by intravital microscopy. Furthermore, isolated human PMNs or whole blood were incubated with each PLA2 inhibitor and then activated with formyl-methionyl-leucyl-phenylalanine (fMLP) or PAF. PMN adherence was assessed by counting cells bound to purified fibrinogen, and the surface expression of lymphocyte function-associated antigen 1 and macrophage antigen 1 (Mac-1) was measured by flow cytometry. RESULTS: The iPLA2 γ-specific inhibitor almost completely inhibited the fMLP/PAF-induced leukocyte adherence in vivo and in vitro and also decreased the fMLP/PAF-stimulated surface expression of Mac-1 by 60% and 95%, respectively. In contrast, the other inhibitors did not affect these cellular functions. CONCLUSION: iPLA2 γ seems to be involved in leukocyte/PMN adherence in vivo and in vitro as well as in the up-regulation of Mac-1 in vitro in response to PAF/fMLP. This enzyme is therefore likely to be a major regulator in the PMN recruitment cascade.